Christian Apologetics through African Eyes - Kigame, Reuben (Posterity Publishers, 2018)
One of the ultimate questions of human existence is: ‘Why am I here?’ Reuben Kigame declares his identity as fully African and fully Christian to share his mission: ‘I am put here for the defense of the Gospel’. Drawing on a wealth of information and years of interaction and reflection, Reuben Kigame has given us a wide-ranging reference work that will receive a deservedly warm welcome wherever current and future African apologists are to be found. Read this book and see how clear-eyed and sharp-witted Reuben is!
Keywords: Africa; Apologetics; Christianity; Evangelistic work